Marketing Analysis of Buffalo at the Animal Market in Suka Village Karo Regency - A. H. Daulay; E. Mirwandhono; Sianturi, R. Br. (Talenta Publisher, 2022)
Buffalo is one type of ruminant livestock that has quite a lot of potential. The animal market is a place for transacting buying and selling animals, which includes cows, buffaloes, goats and sheep. Animal markets usually operate only a few days a week. The Animal Market in Suka Village, Tigapanah District, Karo Regency is an animal market that operates every Tuesday from 09.00 - 17.00 WIB. Livestock sold in this animal market are cows and buffalo. Producers and consumers conduct transactions directly. This animal market is one of the potential areas of Karo Regency in the field of animal husbandry and is very suitable for developing buffalo marketing. This study aims to identify the characteristics of buffalo marketing institutions, market behavior, pricing processes, marketing channels, the role of the government in the animal market, analysis of margins marketing farmer share, and to analyze the marketing efficiency of buffalo in the animal market of Suka Village, Karo Regency. This research was conducted in October 2019-November 2019. The method used in data collection was descriptive analysis based on surveys and observations made, while the sample of farmers and other marketing institutions was snowball sampling. Data was collected by using interview techniques using questionnaires. The results of this study are that the marketing institutions involved include breeders and traders who are all male, whose age is above productive < 51. There are two marketing channels, namely the first channel: farmers - consumers and the second channel: breeders - collectors - consumers. Marketing functions carried out by marketing institutions are exchange, physical and facility functions. Market behavior is that there is no dishonesty in pricing, marketing costs are not uniform and there is no government intervention. The market performance is that there is no technological progress, there is no improvement in product quality and service maximization. Data analysis includes marketing costs, marketing margins, farmer share of costs from each marketing channel. The results of this study indicate that there are two marketing channels. Margin is obtained by a marketing channel that has one marketing agency, thus this marketing channel has the farmer's share . So it can be concluded that the first marketing channel is the most efficient channel because it has the smallest cost and big profit.